DI SEPUTAR percakapan pendidikan dalam Muhammadiyah / Noeng Muhadjir ; penyunting, Imron Nasri, A. Hasan Kunio - Kunio, A. Hasan; Nasri, Imron; Muhajir, Nung (Pustaka SM, 1994)
viii, 127 hlm. : ilus. ; 20 cm.